Letters from Sixt Birck to Oswald Miconius of 1532-1536s: introductory article, Russian translation AND commentary - Zinaida Andreevna Lurie (Религия, церковь, общество, 2013)
The author cites the original text and Russian translation of the letters of the German playwright Sixt Birk to the Basel humanist Oswald Miconius written from the collection of the Zurich library. The introductory article introduces the reader to the biography of Birka, which is not well studied. The publication represents three of the four letters of the collection, which date from 1532–1536 (unpublished refers to 1548.). The material of the letters provides an opportunity for extensive generalizations related to the relationship of the intellectual with the urban elite during the confessionalization period. The published correspondence with Oswald Miconius reflects Birk’s attempt to acquire a patron in an intellectual environment. This was especially important for Birk at the beginning of his career, and it became especially relevant due to a personal conflict with one of his students. In 1536, apparently, having failed to completely overcome the conflict, Birk returned to Augsburg, where he probably hoped for a more benevolent attitude.